The Role of Ma'riful Quran in Shaping Contemporary Islamic Thought in Bangladesh: An Analysis of Mufti Mohammad Shofi's Contributions - Aflatun Al-Kausar (Bulletin of Islamic Research, 2024)
Aim: This study examines the impact of Mufti Mohammad Shofi's 'Ma'riful Quran' on contemporary Islamic thought in Bangladesh. It aims to analyze the methodology, reception, and influence of Shofi's Tafsir within academic, religious, and social contexts. Methods: This research synthesizes scholarly critiques, educational integration, and societal reception of the 'Ma'riful Quran' through a comprehensive literature review. It also explores Shofi's interpretative approach, sources, and the thematic relevance of his exegesis. Findings: The 'Ma'riful Quran' has significantly influenced Islamic education by integrating traditional scholarship with modern relevance. It has garnered widespread acceptance in Bangladesh, shaping pedagogical practices and fostering a balanced understanding of the Quran. Despite criticisms regarding scholarly rigor and interpretative nuances, Shofi's Tafsir remains a pivotal resource for understanding and applying Quranic teachings in contemporary contexts. Implications: The study underscores the importance of accessible yet scholarly Tafsir works in promoting moderate Islamic discourse and addressing societal challenges. 'Ma'riful Quran' is a model for bridging classical interpretations with contemporary issues, offering practical guidance for Muslims in Bangladesh and beyond.Conclusion: Mufti Mohammad Shofi's 'Ma'riful Quran' exemplifies a significant contribution to Islamic scholarship in Bangladesh. It navigates the complexities of Quranic exegesis while engaging with modern realities. Its impact on education, religious discourse, and societal ethics underscores its enduring relevance in shaping Islamic thought and practice.